Dari Amanat Agung ke Media Digital: Analisis Bibliometrik Periode 2014-2023 tentang Misi Kristen Global - Suparta, I Ketut Gede; Nicholson, Foret (Jurnal Teologi Kontekstual Indonesia, 2024)
This bibliometric analysis aims to explore the literature on Christian Missions published between 2014 and 2023, with a focus on identifying research trends, key themes, and influential authors in the field. This analysis seeks to understand the evolving landscape of Christian Mission studies and its implications for future research. This analysis uncovers significant trends in Christian Missions research, including publication rates that fluctuate with peaks around 2019 and 2021. Dominant themes include the integration of digital media in mission work, cultural approaches to evangelism, and social justice initiatives in mission contexts. Key authors and institutions are identified, highlighting the collaborative networks that shape the discourse in this field. These findings underscore the importance of understanding Christian Mission as a dynamic field that intersects with cultural, social, and technological change. There are important gaps in the literature regarding emerging trends in digital evangelism and holistic mission approaches that require further exploration.